2012
DOI: 10.1088/0004-6256/144/5/130
|View full text |Cite
|
Sign up to set email alerts
|

Projected Rotational Velocities and Stellar Characterization of 350 B Stars in the Nearby Galactic Disk

Abstract: 1 braganca@on.br -2 -Projected rotational velocities (v sin i) are presented for a sample of 350 early B-type main sequence stars in the nearby Galactic disk. The stars are located within ∼ 1.5 kpc from the Sun, and the great majority within 700 pc. The analysis is based on high-resolution spectra obtained with the MIKE spectrograph on the Magellan Clay 6.5-m telescope at the Las Campanas Observatory in Chile. Spectral types were estimated based on relative intensities of some key line absorption ratios and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 35 publications
4
38
0
Order By: Relevance
“…Based on spectroscopic studies, Bragança et al (2012) reported that the star has V sin i = 86 km s −1 , similar to the half-width of the CCF peak. However, Bragança et al (2012) estimate that the star's temperature is T eff = 19.6 kK, and we would usually expect little correlation with the features of such a relatively cooler object. However, the CCFs show no significant peak velocity variations.…”
Section: Discussionmentioning
confidence: 66%
“…Based on spectroscopic studies, Bragança et al (2012) reported that the star has V sin i = 86 km s −1 , similar to the half-width of the CCF peak. However, Bragança et al (2012) estimate that the star's temperature is T eff = 19.6 kK, and we would usually expect little correlation with the features of such a relatively cooler object. However, the CCFs show no significant peak velocity variations.…”
Section: Discussionmentioning
confidence: 66%
“…1,ab): υ sin i measurements in the Galaxy and in the Magellanic Clouds indicate that these are rapidly rotating stars, with a mean projected velocity of about 130 km.s −1 for B-type stars (Bragança et al 2012, Hunter et al 2008b, Mokiem et al 2006, Abt et al 2002, and about 110 km.s −1 for O-type stars (Penny 1996, Penny & Gies 2009). Some stars in the On subtype (with nitrogen enrichment) can reach projected velocities of about 420 km.s −1 (Walborn et al 2011) but the number of these very rapid rotators is actually limited.…”
Section: Measurements Of Stellar Rotationmentioning
confidence: 93%
“…In the blue part, R ∼ 53 000. The spectral reduction was carried out using the Carnegie Observatories python pipeline 2 (Bragança et al 2012;Garmany et al 2015). …”
Section: Sample Observations and Data Reductionmentioning
confidence: 99%
“…To further validate our method, we compared the v sin i for eight stars with those obtained by Bragança et al (2012) and Garmany et al (2015) with a different method based on the full width at half-minimum [FWHM] of He i lines. The results are presented in Table 1: they show a good agreement within errors, although there is some indication of slightly larger values in our case.…”
Section: Rotational Velocitiesmentioning
confidence: 99%